Dairy Product Consumption and Oligo-Astheno-Teratozoospermia Risk: A Hospital-Based Case-Control Study in China - Xiao-Bin Wang; Qi-Jun Wu; Qi-Jun Wu; Ren-Hao Guo; Xu Leng; Qiang Du; Yu-Hong Zhao; Yu-Hong Zhao; Bo-Chen Pan (Frontiers in Nutrition, 2021)
Background: Researches on the association of dairy products consumption with Oligo-astheno-teratozoospermia (OAT) risk has been limited and controversial. Therefore, we aim to explore the aforementioned association among Chinese men.Methods: A hospital-based case-control study was conducted in men consisting of 106 cases of OAT and 581 controls. Intakes of dairy products and their related nutrients were collected using a semi-quantitative food frequency questionnaire and semen quality was analyzed according to the World Health Organization guidelines. The daily intake of dairy products and their related nutrients was categorized into three groups with the lowest tertile serving as the reference category. Odds ratios (ORs) and 95% confidence intervals (CIs) of association between dairy intake and OTA risk were calculated by the multivariable logistic regression models.Results: No significant association was found between total dairy (OR T3vs.T1 =1.53, 95% CI: 0.85–2.78), protein (OR T3vs.T1 =1.51, 95% CI: 0.84–2.75), or calcium (OR T3vs.T1 = 1.46, 95% CI: 0.81–2.66) and the OAT risk in the main findings. However, we observed a statistically significant positive association of dairy fat intake with OAT risk (OR T3vs.T1 =1.93, 95% CI: 1.06–3.58). The findings were consistent with the main results when we carried out subgroup analysis stratified by body mass index.Conclusion: A significant positive association was found between dairy fat intake and the risk of OAT. Further large-scale prospective studies are required to confirm this finding.